The The discursive strategies of power and female resistance in margret atwood's the handmaid's tale: a foucauldian reading - Henir Ismael; Hasan Saleh (گۆڤارا زانستێن مرۆڤایەتی یا زانكۆیا زاخۆ, 2023)
This paper examines the use of certain discursive strategies and the consequent female resistance in Margret Atwood novel The Handmaid's Tale (1985. The novel portrays different forms of power exercised by totalitarian governments over women. In complex ways, Margret Atwood uses the feminist dystopian genre to resist gender-based oppression. To do so, Atwood must first build a miserable world that subjugates their female characters before she can create ways for these characters to resist. The events of The Handmaid's Tale, like most dystopian stories, take place in the future, but they express the anger and anxieties of the present, and more women speak out against sexual assault and harassment. This study applies Michel Foucault's concepts of power relations through discursive strategies in Margret Atwood's “The Handmaid’s Tale”. More explicitly, the research tries to shed light on the discursive practices used to control women's minds and bodies in a way that guarantees complete obedience to a specific ideology. The study also shows how women use strategies of language and education to resist and free themselves from the oppression imposed on them. These types of fiction have always been sites of power conflict, reflecting the atrocities committed against the public by those in power. It is concluded that Foucault's ideas about discourse and power explain why women are oppressed by totalitarian regimes and how they use the same power to build a discourse of resistance to free themselves from oppression and disciplinary power.